Cricopharyngeal myotomy with thulium laser through flexible endoscopy: proof-of-concept study - Siboni, Stefano; Aiolfi, Alberto; Ceriani, Chiara; Tontini, Gian Eugenio; Bonavina, Luigi (Endoscopy International Open, 2018)
Background and study aims Endoscopic treatment of Zenker’s diverticulum has proven feasible, but electrocautery and CO2 laser technology carry the risk of collateral thermal injury. Thulium laser septum incision may overcome this limitation. We describe for the first time the use of thulium laser through flexible endoscopy in a small cohort of patients with Zenker diverticulum.Patients and methods Thulium laser septum division was performed via flexible endoscopy under general anesthesia in consecutive symptomatic patients with primary or recurrent Zenker diverticulum. Primary study outcomes were feasibility and safety of the procedure. A 1.9-μm laser fiber was used with an emission power of 10 – 16 W. Results Five patients were treated between May and June 2017. Two patients presented with recurrent symptomatic diverticulum after previous transoral septum stapling. Complete division of the septum was achieved in all patients. There was no bleeding nor need of adjunctive electrocautery devices to complete the procedure. The postoperative course was uneventful in all patients; the chest film and gastrographin swallow study on postoperative Day 1 were negative for pneumomediastinum, leaks or residual pouch. All patients were discharged within 48 hours on a soft diet. At the 1- and 3-month follow-up visits, all patients were satisfied with the procedure and reported improved swallowing and absence of regurgitation and cough.Conclusions Division of Zenker’s septum with thulium laser is feasible and safe through flexible endoscopy. Longer-term follow-up is required to establish efficacy and effectiveness of this novel procedure.